Disease-modifying osteoarthritis drugs: in vitro and in vivo data on the development of DMOADs under investigation. (April 2013) - Davies, Peter SE; Graham, Simon M; MacFarlane, Robert J; Leonidou, Andreas; Mantalaris, Athanasios; Tsiridis, Eleftherios
<x xml:space="preserve">Abstract</x> Introduction: Osteoarthritis is a disabling affliction, and disease-modifying osteoarthritis drugs (DMOADs) would be highly desirable adjuncts to symptomatic relief as they may delay the disease process. Areas covered: This study is a comprehensive review of the recent literature on the efficacy of DMOADs in the treatment of OA. In vitro and in vivo evidence was collected using MEDLINE® (1950 to November 2012) and EMBASE (1980 to November 2012) databases. Several drugs have demonstrated DMOAD effects in OA. They can be divided into three groups based on their predominant mode of action: those targeting cartilage, inflammatory pathways and subchondral bone. OARSI guidelines recommend glucosamine and chondroitin sulphates and diacerein as DMOADS, and NICE will recommend glucosamine sulphate in the next update of guidelines. Exploration of improved outcome measures and identification of subgroups of patients most likely to benefit from different DMOADs are likely to be the most important areas of development over the coming years. Expert opinion: It is expected that a wider range of prospective clinical studies will be embarked upon in the coming years. Trials including MRI as well as joint space narrowing (JSN) should be designed in a systematic manner, powered with sufficient numbers to demonstrate clinical benefit at different stages of disease.